Fiqh Muamalah Review of The Kali Lubang Tutuik Lubang System in Farm Labor Wages - Putri, Siska Elasta; Wahyudi, Syafri; Nofialdi, Nofialdi (Institut Agama Islam Negeri Kerinci, 2021)
This paper examines the practice of remuneration of farm laborers with the kali lubang tutuik lubang system in the perspective of fiqh muamalah. This research uses qualitative method with descriptive research type. This research was conducted in Nagari Lawang Mandahiling, Tanah Datar Regency, West Sumatra. The data in this study consisted of primary data and secondary data. Data were analyzed using interactive model of analysis, starting from data collection, data reduction, data presentation, and drawing conclusions. This research shows that the wage contract with the kali lubang tutuik lubang system is in the form of a speech containing an agreement about the type of work, place, and time of work. Wages are not paid directly by the land owner on the first day, but on the second day or when the worker gets a second job from the same person. If there is no work on the second day or other work, wages will be deferred one week from the last day of work. According to the fiqh muamalah review, wages with this system are legal, because from a legal point of view, the contract has met the terms and conditions. Both parties also understand that the system has been going on for a long time. However, from an ethical aspect, such a wage system contains demages, because it contains elements of neglecting the payment of wages.